Repercussões e enfrentamento da doença e tratamento na vida de pessoas em hemodiálise no município de Patos-PB. - Brito, Polianne Medeiros (2016)
Introduction: Chronic renal disease is considered nowadays, as one of the main public health problems in the world, being an important cause of morbidity and mortality. The diagnosis leads to the need for continuous treatment, submitting the patient to a constant coming and going to the hospital, and this impacting and wearing routine, many times moves the individual partially or totally away from work activities, bringing consequences with the family income, limiting their lives in many aspects, submitting the individual to the dependence of the family or health service. Objective: To analyze from the perspective of the patient with chronic renal disease, the repercussions of the disease and strategies to confront the treatment in a hemodialysis unit in the municipality of Patos-PB. Methodology: This was a qualitative study with chronic renal patients who were in hemodialysis treatment in a private clinic in the municipality of Patos-PB, where SUS (which is a Unified Health System) is the financial transfer so that the carriers are not charged for the treatment. The data was collected by means of a semi-structured interview, in the pre-dialysis period. Preliminary information regarding the study was provided, the signature of the informed consent form was requested and then the interview was recorded with the consent of the participants and fictitious names were used. After the collection, the interviews were transcribed and categories and sub-categories were established for Bardin¿s qualitative content analysis. Results: 06 chronic renal disease patients were interviewed; where, 03 were men and 03 were women in hemodialysis treatment, ageing between 20 to 55 years. The majority of the participants were single and catholic, with educational levels varying from illiterate to complete secondary level, none of them were working at the time of the interviews and 05 of them received a health care benefit of a minimum salary. All the interviewed were referred from a public hospital service, with immediate access to the hemodialysis treatment. Changes occurred in the social and daily life, work, feeding and leisure of all the participants. Alterations in general health due to the treatment were also reported by the majority of the clients. The main confrontation strategies found to deal with the disease and the treatment were the support of the family, partners, and religion. The main difficulties to start and maintain the hemodialysis treatment were the lack of knowledge about the disease and the treatment and the lack of transportation, in order to dislocate the patients to the hemodialysis service .The friendly reception of the multi-professional team, faith and the support of the family and other clinically well patients, were pointed out as being facilitator factors to start and maintain the treatment. Conclusion: the study revealed that the chronic renal disease causes great repercussions in the life of the hemodialysis patients, altering their lifestyle and daily routine; the support of the family, religion and the multi-professional team represented the main confronting strategies for the adhesion to and maintenance of the treatment of the interviewed patients.